Modified technique of submandibular gland transfer followed by intensity modulated radiotherapy to reduce xerostomia in head and neck cancer patients. Issue 9 (13th May 2020) - Chang, Chia‐Fan; EI‐Sayed, Ivan H.; George, Jonathan R.; Heaton, Chase M.; Ryan, William R.; Susko, Matt S.; Yom, Sue S.; Ha, Patrick K.
Abstract: Background: Xerostomia is one of the most common long‐term adverse effects of radiotherapy for head and neck cancer patients. Contralateral submandibular gland transfer (SMG‐T) before radiotherapy was shown to reduce xerostomia compared to pilocarpine. We sought to evaluate a modification of this surgery preserving the ipsilateral facial artery and vein to simplify the SMG‐T. Methods: Eighteen patients planned for head and neck intensity modulated radiotherapy to both necks were reviewed. Surgical complications were recorded. The grade of xerostomia was assessed after treatment completion. Results: There were no minor or major complications resulting from the modified SMG‐T. At 24.5‐months follow up, the incidence of post‐treatment moderate to severe xerostomia was 16.7%. No locoregional recurrence occurred. Only one patient had distant solitary lung metastasis. Conclusion: The modified SMG‐T technique is a practical and effective method to reduce the dose of radiation to the contralateral SMG and limit post‐treatment xerostomia.